Ageing in a foreign land: Stressors and coping strategies in the discourse of older adult Spanish speakers in Australia. Issue 1 (1st March 2020) - Rojas-Lizana, Sol; Cordella, Marisa
Using discourse analysis we explore the connections between ageing and coping in the discourse of culturally and linguistically diverse (CALD) older Spanish speakers in Australia in relation to the stressor 'uncertainty about future care'. We examined nineteen semi-structured interviews of CALD seniors living in Brisbane to identify and analyse discursively the coping strategies that they used when talking about future care giving. The results indicate that the participants use active and passive coping strategies to deal with their stressors. The active strategies favour a connection between family members and community support, while the passive strategies show a level of self-protective resignation about what the future holds for them by resorting to religious comfort. Although participants express preference for the way care was provided to older people in their country of origin, they also seem resigned to their children adopting Anglo-Australian customs, and justify this choice as an unavoidable product of cultures in contact.